Empowering Mind Mapping Strategy To Improve Students’ Writing Skills In The EFL Classroom - Mantra, Ida Bagus Nyoman; Handayani, Nengah Dwi; Widiastuti, Ida Ayu Made Sri (Denpasar Institute, 2021)
Writing is one of the important language skills to communicate in written forms. Therefore, the improvement of writing skills is absolutely essential to be continually carried out. This study aims at developing writing skills by implementing a mind mapping strategy in the EFL classroom. There two cyclic learning sessions comprising planning, action, observation, and reflection were conducted in this study. The data were collected through administering pre-test, post-test, and questionnaires to the students who participated in this study. Based on the results of data analysis, this study revealed that students’ writing skills could be improved through implementing a mind mapping strategy. Therefore, this study implies that teachers should consider using mind mapping in teaching writing